A Description of Knowledge About Bullying, Bullying Perpetrators, Bullying Victims, Teenagers at Pancur Batu Methodist High School 2022 - Heny Melasari manik; Risda Mariana Manik; Desriati Sinaga (Sean Institute, 2022)
Problem of bullying is n't it only are you serious for the parties who become victims, but is problem big for all. Victims of bullying can change Becomes bullies in the future day. Bullying is something more action show aggressive behavior and manipulative, which can be conducted by one person or more to show to others, often containing violence and show existence imbalance strength between victim and bullies. For knowing picture knowledge about bullying, perpetrators of bullying, victims of bullying, Teens At Methodist High School pancur batu 2022. Engineering taking sample that is Acidental Sampling in which the sample is taken by See you soon, technique this based on which accidental there is or which ready for researched as much as 30 respondents. The research instrument used a questionnaire in the form of a google form. Results picture knowledge about bullying showing part big have category knowledge good as many as 16 people (53.3 % ). Description perpetrator bullying shows part big have not category perpetrator bullying as many as 29 people (96.7 % ). Description victim bullying shows part big have category not a victim bullying as many as 26 people (86.7%). his height level knowledge teenager about bullying, then the more low level bullying incident, on the other hand the more low level knowledge teenager about bullying so the more tall level bullying incident. In this case, it is suggested to the school to pay more attention to those who are victims of bullying so that victims feel cared for and comfortable during school.